2013
DOI: 10.1104/pp.113.231605
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Multiple Genes Encoding ADP-Glucose Pyrophosphorylase Subunits in Maize Endosperm, Embryo, and Leaf      

Abstract: ADP-glucose pyrophosphorylase (AGPase) provides the nucleotide sugar ADP-glucose and thus constitutes the first step in starch biosynthesis. The majority of cereal endosperm AGPase is located in the cytosol with a minor portion in amyloplasts, in contrast to its strictly plastidial location in other species and tissues. To investigate the potential functions of plastidial AGPase in maize (Zea mays) endosperm, six genes encoding AGPase large or small subunits were characterized for gene expression as well as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 65 publications
6
78
0
1
Order By: Relevance
“…Yellow nutsedge is a monocot that is more closely related to cereals than to dicots. However, previous studies have indicated that the AGPS gene in cereals is generally comprised of ten exons and nine introns (Huang et al, 2013); alternately, AGPS in cotton (Taliercio, 2010) and Arabidopsis (Hadrich et al, 2012) expressed a nine exon-eight intron structure, similar to that seen in this study.…”
Section: Cloning and Sequence Analysis Of Yellow Nutsedge Agps Genesupporting
confidence: 81%
See 1 more Smart Citation
“…Yellow nutsedge is a monocot that is more closely related to cereals than to dicots. However, previous studies have indicated that the AGPS gene in cereals is generally comprised of ten exons and nine introns (Huang et al, 2013); alternately, AGPS in cotton (Taliercio, 2010) and Arabidopsis (Hadrich et al, 2012) expressed a nine exon-eight intron structure, similar to that seen in this study.…”
Section: Cloning and Sequence Analysis Of Yellow Nutsedge Agps Genesupporting
confidence: 81%
“…Although the integral enzyme activity is a function of both subunits, previous studies have shown that the small subunit alone could form a homotetramer (α 4 ) and be active under saturating concentrations of substrates and 3-PGA (Ballicora et al, 1995). The ADPGlcPPase small subunit (AGPS) gene has been identified in various higher plants ( Thorbjornsen et al, 1996;Okita et al, 2001;Rosti et al, 2006;Rösti et al, 2007;Taliercio, 2010;Huang et al, 2013). In barley and rice (Okita et al, 2001), a single gene can encode two different transcripts for AGPS, whereas in maize, two paralogous genes encode two different AGPSs (Rösti et al, 2007).…”
mentioning
confidence: 99%
“…Banana AGPL genes were found only in two of the four Angiosperm AGPL sub-families identified by phylogenetic analysis (AGPLI and AGPLIII, Figure 1A ). These AGPLI and AGPLIII sub-families include known functional AGPL subunits (e.g., AtAPL1, AtAPL3, AtAPL4, agplIzm, ZmSH2, agplemzm; Crevillen et al, 2003; Huang et al, 2014) and have members in all analyzed species. In contrast, AGPLII and IV show gene loss in several lineages ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst the AGPase subunits identified represent the cytosolic enzyme in maize, and therefore would be unlikely candidates to interact with starch synthases, it is possible that, in vivo, the plastidic isoforms are directly involved. We do not know which domains of the AGPase large and small subunits are involved in proteinprotein interactions, but there is a good degree of functional and structural similarity between the cytosolic and plastidic sequences (Huang et al 2014). The cytosolic enzyme accounts for approximately 99 % of the total AGPase activity (Denyer et al 1996) which may explain why the plastidic isoform was not readily detected in these protein-interaction experiments in vitro.…”
Section: Biochemical Evidencementioning
confidence: 98%